(untitled) (Third Sector Social Economic Review, 2024)
This study examines the importance of green bonds for municipalities’ sustainability projects and their role in providing financing. It emphasizes that green bonds offer a significant resource for municipalities to achieve their sustainability goals and have the potential to create environmental and social impacts. Additionally, it is stated that municipalities address environmental issues and generate social benefits by issuing green bonds. The study aims to contribute to a better understanding of the potential of green bonds among municipalities and to enhance knowledge sharing in this field. In this context, discount rates that municipalities can use in their investment projects are proposed, and the importance of these rates in terms of alternative options is highlighted. Thus, it is aimed to facilitate easier financing of sustainable projects for municipalities. To enable more effective use of green bonds, educational and awareness programs for municipalities should be organized. Moreover, municipalities could be encouraged to issue green bonds by providing specific incentives or tax advantages for sustainable projects. Green bonds are considered a long-term financing tool that municipalities can use to achieve their environmental sustainability goals. These bonds, which can be used to finance projects such as energy efficiency, renewable energy, and water management, can also help municipalities mitigate environmental risks. Therefore, the use of green bonds by municipalities should be promoted. Municipalities can collaborate with experts to develop green bond policies and take more effective steps toward achieving their environmental sustainability goals.